John Lewis Burckhardt’s Nile Journeys and Nubia - Selda Güner Özden (Şarkiyat Mecmuası)
Africa, which until the eighteenth century oscillated between myth and reality in the eyes of Europeans, became the subject of modern research after it came under the influence of colonialism. Nubia, which was the subject of conflict between Egypt and Sudan after its conquest by Mehmet Ali Pasha in 1841, also became a subject of colonial curiosity. By focusing on the observations of Swiss traveler John Lewis Burckhardt (1784-1817), this study examines the socioeconomic and cultural history of Nubia, which has not been addressed adequately in Turkish historiography. Burckhardt’s travels to Bilad al-Sham, Egypt, Nubia, and Arabia between 1809 and 1816 on behalf of the African Association and the notes he kept during those travels constitute the main material of this study. Furthermore, this paper analyzes Burckhardt’s Travels in Nubia (1819), a compilation of his journals and letters, to evaluate his anthropological observations of nineteenth-century Nubia. This article also examines the curiosity and desire for exploration that motivated a European traveler to embark on a challenging journey of discovery in Africa and the role of the African Association in his voyage to the region.